Nutrition and quality of life in children with Type 1 Diabetes Mellitus (Research, Society and Development, 2022)
Type 1 diabetes mellitus (DM1) is a multifactorial disease, which generally occurs due to genetic factors that, in the presence of an environmental factor, end up triggering this aggression against pancreatic antigens. DM1 can affect people of any age, appearing more frequently up to the age of 30, and generally affecting children and adolescents. The objective of this work was to analyze the impacts of the treatment of type 1 diabetes in the lives of children with the disease. An integrative literature review was carried out, analyzing scientific articles, books, theses and monographs, with publication period between the years 2003 and 2021, in English, Spanish and Portuguese, through the SCIELO, PUBMED and Capes Periodicals databases. . The search was performed by the descriptors, type 1 diabetes mellitus, children, parents, psychological and social. In view of the analysis of the studies, the importance of adequate and specific care for children diagnosed with type 1 diabetes mellitus is evident, since the studies presented identify that the support network formed by family, friends and a multidisciplinary team, as well as The practice of physical activity is of paramount importance for children with DM1 to have effective control of the disease. Regarding the nutrition of children with the disease, fewer studies were found, they point out that the consumption of diets with higher protein content, lower saturated fat content and low glycemic index carbohydrates and glycemic load, helped in better control of the disease. illness.